2015
DOI: 10.1002/2015gl065169
|View full text |Cite
|
Sign up to set email alerts
|

Model insights into energetic photoelectrons measured at Mars by MAVEN

Abstract: Photoelectrons are important for heating, ionization, and airglow production in planetary atmospheres. Measured electron fluxes provide insight into the sources and sinks of energy in the Martian upper atmosphere. The Solar Wind Electron Analyzer instrument on board the MAVEN (Mars Atmosphere and Volatile EvolutioN) spacecraft measured photoelectrons including Auger electrons with 500 eV energies. A two‐stream electron transport code was used to interpret the observations, including Auger electrons associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 23 publications
0
66
0
Order By: Relevance
“…849 since an Interplanetary Coronal Mass Ejection (ICME) was observed during this orbit (Curry et al 2015;Dong et al 2015). According to the model results of Sakai et al (2015), invoking a population of external SW electrons is sometimes required to interpret the electron energy spectrum observed at the dayside of Mars, a situation that is beyond the scope of this study. To be conservative, we exclude all orbits displaying strong fluctuations in ionization efficiency.…”
Section: Calculation Of Ionization Efficiencymentioning
confidence: 95%
See 2 more Smart Citations
“…849 since an Interplanetary Coronal Mass Ejection (ICME) was observed during this orbit (Curry et al 2015;Dong et al 2015). According to the model results of Sakai et al (2015), invoking a population of external SW electrons is sometimes required to interpret the electron energy spectrum observed at the dayside of Mars, a situation that is beyond the scope of this study. To be conservative, we exclude all orbits displaying strong fluctuations in ionization efficiency.…”
Section: Calculation Of Ionization Efficiencymentioning
confidence: 95%
“…The above sources of data, publicly available at the MAVEN Science Data Center (https://lasp.colorado.edu/maven/sdc/public/), are utilized in this study to determine the ionization efficiency, which is then compared with existing model results (e.g., Fox & Yeager 2006;Haider et al 2006;Nicholson et al 2009). The present study is complementary to various modeling efforts made to understand the photoelectron energy spectrum observed near Mars (e.g., Sakai et al 2015;Peterson et al 2016), but with a special emphasis on secondary ionization as an important effect of photoelectron production. The results presented here are useful for fast calculations of the ionization rate in the dayside Martian upper atmosphere, without the need to construct photoelectron transport models.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Photoelectron transport has been studied for other planets and Moons (e.g., Gan et al, 1990;Richard et al, 2011;Ozak et al, 2012;Sakai et al, 2015 ). The photoelectron transport for Saturn is not easy to study due to the lack of observations, but it has been modeled (e.g., Moore et al, 2008;Galand et al, 2009 ).…”
Section: Comparison With Observations and Previous Modelsmentioning
confidence: 98%
“…Fox and Dalgarno , ]. Sakai et al [] showed that both external electrons from the magnetosheath and solar soft X‐ray irradiance inputs contribute to the high‐energy photoelectron flux in the ionosphere and that the photoelectron flux for energies less than 10 eV, related to the ionospheric electron heating, depends on the ionosphere's electron to neutral density ratio. The electron temperature in the upper atmosphere is controlled by suprathermal/photoelectron heating, by collisional cooling, and by conductive heat transport.…”
Section: Introductionmentioning
confidence: 99%